2021
DOI: 10.1007/s00265-020-02959-1
|View full text |Cite
|
Sign up to set email alerts
|

Extent of threat detection depends on predator type and behavioral context in wild samango monkey groups

Abstract: Detecting predators requires information, and many behavioral and environmental features are predicted to enhance or limit an animal's ability to learn about potential danger. Animals living in groups are thought to be at an advantage for learning about predator presence, but individual safety also depends on cues spreading from detectors to non-detectors as unsuspecting individuals may still be vulnerable. In this study we simulated predator presence among two groups of wild samango monkeys (Cercopithecus alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
(98 reference statements)
2
6
1
Order By: Relevance
“…However, the intensity of effects on the individuals varied with the type of predator model; overall, the tiger model elicited a stronger response than the snake model. This observation was in line with previous studies that showed varying antipredator responses to different predators (LaBarge et al, 2021; Lemasson et al, 2009). Barbary macaques were found to display antipredator behavior even to play‐backs of dog alarm calls, whereas snake alarm calls failed to elicit a response (Fischer & Hammerschmidt, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the intensity of effects on the individuals varied with the type of predator model; overall, the tiger model elicited a stronger response than the snake model. This observation was in line with previous studies that showed varying antipredator responses to different predators (LaBarge et al, 2021; Lemasson et al, 2009). Barbary macaques were found to display antipredator behavior even to play‐backs of dog alarm calls, whereas snake alarm calls failed to elicit a response (Fischer & Hammerschmidt, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…However, the intensity of effects on the individuals varied with the type of predator model; overall, the tiger model elicited a stronger response than the snake model. This observation was in line with previous studies that showed varying antipredator responses to different predators (LaBarge et al, 2021;Lemasson et al, 2009).…”
Section: Predator Type and Hand Preference As Predictors Of Behaviora...supporting
confidence: 93%
“…Previous studies with this group indicate that animals perceive less risk from terrestrial predators when near humans (Nowak et al, 2014), and studies on terrestrial predators like leopards (Van Cleave et al, 2018) indicate that these animals tend to avoid people. Unfortunately, we could not identify differences in responses between predator types, although some evidence indicates that this study population tends to respond more intensely to leopards and eagles than snakes (LaBarge et al, 2021). Additionally, with such a large study group, individuals are less likely to be near a single observer for long periods of the day.…”
Section: Effects Of Humans Predators and Competitorsmentioning
confidence: 82%
“…This suggests that conspecific aggressiveness is associated with predator-response behaviours in this species, albeit in a non-linear fashion. Responding to a predator quickly and closely could reduce the risk of nest predation, by alerting other group members to the threat and facilitating the performance of distraction displays to draw the predators’ attention ( Kleindorfer, Fessl & Hoi, 2005 ; LaBarge et al, 2021 ; Rowley, 1962 ; Zuberbühler, 2001 ). However, such a strong response would presumably also place the responders at greater risk of being predated themselves, making the net fitness benefits unclear.…”
Section: Discussionmentioning
confidence: 99%